1999
DOI: 10.1007/s002530051421
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective reduction of ethyl 4-chloro-3-oxobutanoate by Escherichia coli transformant cells coexpressing the aldehyde reductase and glucose dehydrogenase genes

Abstract: The asymmetric reduction of ethyl 4-chloro-3-oxobutanoate (COBE) to ethyl (R)-4-chloro-3-hydroxybutanoate [(R)-CHBE] using Escherichia coli cells, which coexpress both the aldehyde reductase gene from Sporobolomyces salmonicolor and the glucose dehydrogenase (GDH) gene from Bacillus megaterium as a catalyst was investigated. In an organic solvent-water two-phase system, (R)-CHBE formed in the organic phase amounted to 1610 mM (268 mg/ml), with a molar yield of 94.1% and an optical purity of 91.7% enantiomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 15 publications
1
71
0
Order By: Relevance
“…In this case, resting cells were used and NAD ϩ or NADP ϩ was externally added to stimulate reactions. Formate dehydrogenase for NADH regeneration (14) and glucose dehydrogenase for NAD(P)H regeneration (23) have often been used in restingcell oxidoreductase reactions. Although the resting-cell reaction is certainly a powerful tool for short-term reactions, several disadvantages emerge when it is applied to longerterm reactions on an industrial scale.…”
mentioning
confidence: 99%
“…In this case, resting cells were used and NAD ϩ or NADP ϩ was externally added to stimulate reactions. Formate dehydrogenase for NADH regeneration (14) and glucose dehydrogenase for NAD(P)H regeneration (23) have often been used in restingcell oxidoreductase reactions. Although the resting-cell reaction is certainly a powerful tool for short-term reactions, several disadvantages emerge when it is applied to longerterm reactions on an industrial scale.…”
mentioning
confidence: 99%
“…Chemicals 2¢,4¢-Dichloroacetophenone (Table 1, 1), m-chlorophenacyl chloride (2), 3¢-methoxyacetophenone (3), 3,4-dimethoxyphenylacetone (4), N-Boc-3-pyrrolidinone (5), methyl 4-bromo-3-oxobutanoate (14), ethyl 4-bromo-3-oxobutanoate (15), isopropyl 4-bromo-3-oxobutanoate (16), octyl 4-bromo-3-oxobutanoate (17), isopropyl 4-cyano-3-oxobutanoate (18)…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…Furthermore, to overcome the biocatalytic reduction it is important to regenerate NAD(P)H. Although there have been many efforts to reproduce NADH with coupling systems using formate/formate dehydrogenase, the enzyme's high cost and low activity [13] has precluded general usage. Recently, Shimizu et al [14] and Kataoka et al [15] reported a recombinant enzyme system consisting of aldehyde reductase of S. salmonicolor or carbonyl reductase of C. magnoliae coupled with an NADPH regenerating system comprising glucose dehydrogenase in a water/ organic solvent two-phase system. They have succeeded in the accumulation of (R)-and (S)-4-chloro-3-hydroxybutanoates ethyl esters from the corresponding ketone.…”
mentioning
confidence: 99%
“…6,7) Preparative application of the asymmetric reduction method requires an e‹cient regeneration system of the coenzyme, NAD(P)H, since E. coli cells do not have a su‹cient amount. 8,9) Kataoka et al 10) and Kizaki et al 11) published reports about an e‹cient production system using E. coli cells co-expressing a carbonyl reductase and glucose dehydrogenase from Bacillus megaterium as a catalyst in an n-butyl acetate W water biphasic system. Alternatively, enantioselective oxidation is also a useful and practical method to produce optically active compounds, such as alcohols, 12) diol, 13) and hydroxy acids.…”
mentioning
confidence: 99%